ECO-FRIENDLY TRANSPORTATION: SOLAR CAR DESIGN FOR COMPETITION- PART II, SUSPENSION, STEERING, AND TRACTION SYSTEMS - Behzad Hamedi; Gunnar Copeland; Xiujie Harry Rui; Kurt Peng; Alex Strizenec; Jianyu Hua; Saied Taheri (International Journal of Innovations in Engineering Research and Technology, 2023)
This paper presents the design and analysis of the Suspension, Steering, and Traction Systems for a solar-powered car, as part of a larger eco-friendly transportation project. The aim of this study is to present a comprehensive overview of the mechanical subsystems, highlighting the design process and addressing the challenges encountered in achieving a balanced performance. The design approach for the Suspension, Steering, and Traction Systems involved careful consideration of various restrictions and parameters to ensure efficiency and effectiveness. Adhering to industry standards, regulations, and best practices, the methodology employed a rigorous design approach to meet the project requirements. Throughout the design process, factors such as weight, stability, and maneuverability are considered to optimize the overall performance of the solar car. The design team has already focused on balancing these factors to enhance the vehicle’s handling, stability, and energy efficiency. By implementing an innovative design process and leveraging state-of-the-art technology, the final product demonstrates good design integrity and is ready for comprehensive performance evaluation. The findings and insights gained from this study contribute to the ongoing development and advancement of solar-powered vehicles, specifically in the areas of Suspension, Steering, and Traction Systems.